2022
DOI: 10.1007/s00167-022-07033-z
|View full text |Cite
|
Sign up to set email alerts
|

No kinematical difference between ultra-congruent and medial-congruent total knee arthroplasty when implanted with mechanical alignment: an in vivo dynamic RSA study

Abstract: Purpose To explore in vivo kinematical behavior of the same total knee arthroplasty (TKA) cruciate-retaining (CR) femoral design with either medial-congruent (MC) or ultra-congruent (UC) inlay using model-based dynamic radiostereometric analysis (RSA). The hypothesis was that there would be comparable kinematics between the two groups. Methods A cohort of 16 randomly selected patients (8 MC Persona Zimmer, 8 UC Persona Zimmer) was evaluated through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Multiple studies have reported superior clinical patient outcomes in MP-TKA compared to PS-TKA [ 1 , 15 , 16 , 17 , 18 ]. In contrast, some other studies have shown no difference between the two groups [ 2 , 19 , 20 , 21 ]. Also, the comparison of in-vivo six-degree-of-freedom (6-DOF) knee kinematic during daily activity such as gait [ 3 , 14 , 22 ], stair climbing [ 23 ], sit-to-stand [ 24 ] between MP-TKA and PS-TKA have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Multiple studies have reported superior clinical patient outcomes in MP-TKA compared to PS-TKA [ 1 , 15 , 16 , 17 , 18 ]. In contrast, some other studies have shown no difference between the two groups [ 2 , 19 , 20 , 21 ]. Also, the comparison of in-vivo six-degree-of-freedom (6-DOF) knee kinematic during daily activity such as gait [ 3 , 14 , 22 ], stair climbing [ 23 ], sit-to-stand [ 24 ] between MP-TKA and PS-TKA have shown inconsistent results.…”
Section: Introductionmentioning
confidence: 73%
“…First, only lunge activity was investigated to compare the difference between MP-TKA and PS-TKA. However, the kinematic differences in some daily activities, such as level walking or sit-to-stand, have been evaluated in previous studies [ 3 , 14 , 20 , 24 ]. Lunge activity was considered to evaluate the implant performance better, especially under high flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on the rationale behind the evolution of the MC polyethylene insert design in providing a greater level of stability with minimum constraint [9, 18, 21]. Alesi et al [1]. reported no difference in medial knee kinematics on comparing Ultracongruent (UC) and MC knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The included number of TKAs in this study was chosen based on previous fluoroscopic experience, but lacking a proper sample size calculation. Studies with a similar primary objective and with a sample size calculation, comparing the kinematics of two variations of the Persona TKA, included fewer TKAs per study group [1,42]. Therefore, the results of this study are still of value.…”
Section: Rommentioning
confidence: 99%